111 Primary Organic vs. Primary Psychogenic Erectile Dysfunction: a Cross-Sectional Study on Patient's Characteristics and Sexual Function from a Tertiary Referral Center. (1st May 2022) - Pozzi, E; Fallara, G; Candela, L; Costa, A; Boeri, L; Capogrosso, P; Schifano, N; Cignoli, D; Colandrea, G; Raffo, M; Cornelius, J; Mattei, A; et al.
ABSTRACT: Introduction: Erectile dysfunction (ED) is defined according to three different aetiological groups: organic, psychogenic and mixed. As most cases have mixed aetiology, EAU guidelines suggests using the terms "primary organic" or "primary psychogenic". Objectives: We aimed to stratify a homogenous cohort of patients seeking medical help for ED for the first time according to the newly suggested classification, and to compare sexual function in the two groups. Methods: Complete sociodemographic and clinical data from 2009 consecutive patients were analysed. All patients completed the International Index of Erectile Function (IIEF) at baseline. According to the presence of risk factors for ED (e.g., age≥ 40 yr, obesity, history of hypogonadism, hypertriglyceridemia and/or hypercholesterolemia, hypertension, cardio-vascular, peripheral vascular, neurological, chronic kidney and hepatic disease, diabetes type 1/2, COPD, hyperthyroidism, low D vitamin, use of recreational drugs, thiazides, b-blockers, antipsychotics, SSRIs and depression or anxiety under medical therapy), patients were categorised into primary organic (≥1 risk factor) or primary psychogenic (0 risk factors) ED. Linear regression analysis assessed the association between the number of risk factors and IIEF severity. Lastly, locally scatterplot smoothing (LOESS) method graphically explored the relationship between number of risk factors and IIEF. Results: 1836 (91.4%) were identified with primary organic ED whereas 173 (8.6%) with primary psychogenic ED. Median (IQR) age was 52 (42-61) vs. 30 (25-36) yr, respectively (p<0.001). The most frequently reported risk factors were smoking (53%), high blood pressure (36%), BMI > 30 (15%) and total testosterone <3ng/mL (14%). Overall, 1387 patients (9.3%) had 1 risk factor, 480 (23.9%) 2, 384 (19.1%) 3 and 577 (28.72%) ≥4 risk factors. Overall, patients with primary organic ED had lower IIEF-SD (7 [6-9] vs. 7 [5-8]; p=0.0012) and -OF scores (9 [6-10] vs. 8 [5-10]; p=0.02). Conversely, IIEF-EF, -IS and -OS domain scores were similar between the two groups. At linear regression analysis, the increasing number of ED risk factors was associated with worse IIEF-tot score (coef. -0.593 p=0.039), -EF (coef. -0.409; p=0.003), -SD (coef. -0.0.85, p=0.017) and -OF (coef. -0.203, p=0.001). Conclusions: One out of ten patients suffer from primary psychogenic ED in the real-life settings. The increasing number of risk factors was linearly associated with lower IIEF scores at presentation.